Pengendalian Kualitas Proses Produksi Telur Puyuh di CV Slamet Quail Farm Menggunakan Pendekatan Statistical Process Control (SPC) - Vingky Kinara Arindy; Gusti Raffly Priatmadja; Hana Nuraprilia; Andika Putra Yunias; Bilqis Dzakirani; Kharisma Fitri Hapsari (Journal of Innovative and Creativity, 2025)
Product quality is a vital aspect in the sustainability of livestock businesses. However, CV Slamet Quail Farm is currently facing a challenge in the form of a high percentage of defective eggs, which has the potential to reduce profitability. This study aims to analyze quality control of quail eggs in cage 1B (Cikembar, Sukabumi Regency) by identifying the dominant types of defects and their root causes. Production data from October 2025 were analyzed using check sheets, histograms, Pareto diagrams, and fishbone diagrams. The results show that the most dominant defects are cracked eggs and soft shells, contributing to approximately 80% of the total damage. The cause-and-effect analysis reveals key priority factors, namely insufficient employee accuracy in following harvesting SOPs and fluctuations in cage environmental conditions that trigger stress in the birds. These findings highlight the need for improvements through stricter enforcement of worker discipline, evaluation of feed quality, and enhanced control of production facilities and environmental conditions. The implementation of these improvements is expected to reduce defect rates and maintain production quality stability